MAHAR PERKAWINAN DENGAN HAFALAN AL-QUR’AN: ANALISIS HERMENEUTIKA HADIS KHALED M. ABOU EL-FADL - Tilawati, Anis (Indonesian Journal of Islamic Literature and Muslim Society, 2019)
The purpose of this study is to analyse the hadith about dowry in marriage. In this hadith, it is mentioned that one form of dowry is memorisation of the verses of the Qur'an, but that is said most recently after there is no more iron ring. An exciting phenomenon today is that the memorisation of the verses of the Koran is used for dowry marriages because it is a place for prestige, to make it look unique and different from the general public. This article will review more deeply the meaning of hadith related to marriage dowry from the perspective of hermeneutics Khaled M. Abou El-Fadl. Besides, this paper will explain the understanding of Muslims today about the traditions of marriage dowry with the memorisation of verses of the Qur'an. This research uses the hermeneutic method of hadith Khaled M. Abou El-Fadl. The findings of this study indicate that today Muslims understand the hadith related to memorising the Qur'an as a marriage dowry through a long process of negotiation and dialectics to influence their behaviour. The talk question is the occurrence of a dialogue between the surrounding culture, with the text of the hadith itself.